Книга о старой Москве. Всполошный звон - Нагибин Юрий Маркович (Репро, 2021)
Экземпляры: БС (20211202) / Инвентарный номер: РТШ55071 / Цена: / Сис.шифр: 63.3(2...) / Авт.знак: Н 16 / ГРНТИ: 03.23 / ББК: 63.3(2-2Мос)